Influence of processed spent bleaching earth on the durability of foamed concrete in acidic environment - R., Othman; Khairunisa, Muthusamy; Youventharan, Duraisamy; S., Mohd Arif (IOP Publishing, 2019)
The present research investigates the durability performance of foamed concrete with PSBE as partial cement replacement upon exposure to acidic environment. A basic control mix of foamed concrete (FC) cube was designed for density of 1600kg/m3 and 30% of PSBE by weight of cement namely as PFC were cast. Then all samples were subjected to water curing for 28 days before immersed in the hydrochloric solution with pH 2 for 1800 hour. The mass loss of the specimens was measured at every 100hr until the end of testing period. The findings show that specimens containing PSBE experienced lower percentage of mass loss as compared to control specimen. The use of PSBE assist in generation of larger amount of calcium silicate hydrate gel through pozzolanic reaction that consume calcium hydroxide, a by- product of hydration process which is susceptible to chemical attack. Generally, integration of PSBE as partial cement replacement enhances the resistance of foamed concrete towards acid attack